2000
DOI: 10.1191/096032700678815918
|View full text |Cite
|
Sign up to set email alerts
|

Repeated acetaminophen dosing in rats: adaptation of hepatic antioxidant system

Abstract: Repeated dosing of acetaminophen (paracetamol) to rats is reported to decrease their sensitivity to its hepatotoxic effects, which are associated with oxidative stress and glutathione depletion. We determined if repeated acetaminophen dosing produced adaptive response of key antioxidant system enzymes. Male rats (Sprague-Dawley, 10 weeks) were given 800, 1200, or 1600 mg/kg/day acetaminophen by oral gavage for 4 days. Liver was assayed for oxidative stress and antio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 27 publications
6
42
2
Order By: Relevance
“…Similar results were obtained in previous studies [15 -18]. Similar results were obtained in different study in hepatic rat GR for acetaminophen (paracetamol) [27].…”
Section: Discussionsupporting
confidence: 92%
“…Similar results were obtained in previous studies [15 -18]. Similar results were obtained in different study in hepatic rat GR for acetaminophen (paracetamol) [27].…”
Section: Discussionsupporting
confidence: 92%
“…Body weight reduction is one of the presenting features in drug-induced liver injury (O'Brien et al 2000) and the significant body weight reduction was found following the PCM induction in the present study. The body weight reduction might be owing to impaired liver function as one of its functions is to breakdown the nutrients and release into the blood stream.…”
Section: Discussionsupporting
confidence: 63%
“…Furthermore, it is highly possible that adzuki extract may eliminate reactive intermediates, since Cardador-Martinez et al (18) have reported that bean hulls exert antioxidative properties, as represented by their capacity to either scavenge free radicals or inhibit lipid peroxidation. The decreases in activities of catalase and GSH peroxidase in AAP-administrated groups suggest the increased lipid peroxide content (19). The hepatic catalase and GSH peroxidase activities in the AAP-treated group were decreased by 23.5% and 11.2%, respectively (Table 3).…”
Section: Resultsmentioning
confidence: 92%